Performance Evaluation of Reactivated Spent Bleaching Earth on Color Reduction of Crude Palm Oil - Irvan Guntara Purba; Martomo Setyawan; Totok Eka Suharto (Journal of Chemical Natural Resources, 2025)
This study aims to evaluate the performance of reactivated Spent Bleaching Earth (SBE) in reducing the color of Crude Palm Oil (CPO). SBE was reactivated through chemical activation using HCl and H2SO4 in single, mixed, and sequential modes, followed by calcination at 600°C, producing Reactivated Spent Bleaching Earth (RSBE A–K) samples. The reactivated materials were characterized using Scanning Electron Microscopy (SEM) to evaluate their surface morphology before being applied to the CPO bleaching process and compared with fresh Bleaching Earth (BE). The results showed that the initial CPO color of 22.0/22.0 (red/yellow) was optimally reduced to 7.6/7.6 using RSBE I, outperforming fresh BE, which reduced the color to 11.0/11.0. RSBE I also exhibited the highest performance among all samples. SEM characterization showed that the reactivation process produced a cleaner surface morphology, supporting the improved adsorption performance of RSBE. These findings demonstrate the potential of reactivated SBE as an efficient and sustainable alternative adsorbent for the palm oil refining industry.